Feeding behaviour of Glossina morsitans morsitans infected with Trypanosoma vivax, Trypanosoma congolense or Trypanosoma brucei - Moloo, S.K. (Cambridge University Press, 1983)
The feeding behaviour ofGlossina morsitans morsitansinfected withTrypanosoma vivax, T. congolenseorT. bruceiwas studied and compared with that of uninfected control tsetse. The following parameters were measured. (1) Mean number of feeds taken in 20 consecutive days; (2) mean rate of blood meal intake in μg/sec of the total days fed; (3) mean weight of blood meal intake/day of the total days fed; (4) mean total blood meal engorgement in 20 days; (5) mean number of probes/day of the days fed; (6) mean frequency of the multiple probe feeds and (7) mean number of pre-feeding probes of the multiple probe feeds. Evidence was found to suggest that the rosettes ofT. vivaxandT. congolensein the proboscis, and colonies ofT. bruceiparasites in the salivary glands, did not significantly alter the feeding behaviour of the vector.